Conceptual Design of Eduvillepreneur for Entrepreneurial Subjects - Diane Christine Fernandez; Junisaelah Naswar; Ainornazirah Abdul Ghani; Amirah Abdul Raffar; Siti Nor Fatin Ahmad Fodzi; Hidayati Ahmad; Nurul Aisyah Lau Huifen Mohd Ridwan Lau; Nurain Syamimi Haziqah Suparman (Malaysia Journal of Invention and Innovation, 2023)
Eduvillepreneur; a user interface (concept sketch prototype) has been generated in order to overcome the issue of passive lectures in entrepreneurship subjects in Malaysian Higher Educational Institutions. This project adapts the iterative process called design thinking initially developed by David Kelly. The process begins with “Empathize”, “Define”, “Ideate”, “Prototype” and “Test”. Brainstorming technique is used and then a prototype was generated using Canva App.  Questionnaires were disseminated to 36 Diploma students that are taking entrepreneurship subjects. IBM SPSS Statistics Version 26 was utilized for analysis purposes. The interface designed using Canva App exclusively caters to students to do online business. The generic features are mostly catered for education purposes. There are three views which are Lecturer, Seller, and Customer. The highest mean value is 4.28 indicating that most of the respondents agree that Eduvillepreneur will help them in understanding entrepreneurial content. Eduvillepreneur interface can be commercialized through collaboration with any potential software developer. This interface is designed to be user-friendly and installed on any digital device. There are no online stores created solely for students taking entrepreneurship subjects in Malaysian Higher Education Institutions. By using this interface, students can engage with customers via online methods plus there are special features for lecturers to monitor and track students’ progress in utilizing this platform. The most significant impact will be on students as the Eduvillepreneur prepares students before going into the real business world through experience in dealing with customers via the online platform. This design layout of Eduvillepreneur could attract collaboration with software developers as well as the government in order to support the government's efforts in producing more young entrepreneurs in Malaysia.